2014
DOI: 10.1007/s10495-014-1063-3
|View full text |Cite
|
Sign up to set email alerts
|

TSPO ligand residence time influences human glioblastoma multiforme cell death/life balance

Abstract: Ligands addressed to the mitochondrial Translocator Protein (TSPO) have been suggested as cell death/life and steroidogenesis modulators. Thus, TSPO ligands have been proposed as drug candidates in several diseases; nevertheless, a correlation between their binding affinity and in vitro efficacy has not been demonstrated yet, questioning the specificity of the observed effects. Since drug-target residence time is an emerging parameter able to influence drug pharmacological features, herein, the interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 80 publications
4
26
0
Order By: Relevance
“…PK 11195 is a specific TSPO ligand, known to affect numerous TSPO functions, similar to the effects of TSPO knockdown by genetic manipulation , applying the covalent TSPO ligand irDE-MPIGA to GBM cells, showed that it takes more than 90 min for irDE-MPIGA (25 nM) to irreversibly saturate all TSPO binding sites; 3 hrs after ligand application ΔΨm collapse was observed; 6 hrs after ligand application externalization of phosphatidylserine was observed and cell viability was reduced. After 24 hrs, de-novo TSPO synthesis was observed [40]. The present study shows that modulation of gene expression in U118MG cells due to PK 11195 occurs hours before these previously reported physiological and phenotypic changes [5,14,35,37,40,52].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…PK 11195 is a specific TSPO ligand, known to affect numerous TSPO functions, similar to the effects of TSPO knockdown by genetic manipulation , applying the covalent TSPO ligand irDE-MPIGA to GBM cells, showed that it takes more than 90 min for irDE-MPIGA (25 nM) to irreversibly saturate all TSPO binding sites; 3 hrs after ligand application ΔΨm collapse was observed; 6 hrs after ligand application externalization of phosphatidylserine was observed and cell viability was reduced. After 24 hrs, de-novo TSPO synthesis was observed [40]. The present study shows that modulation of gene expression in U118MG cells due to PK 11195 occurs hours before these previously reported physiological and phenotypic changes [5,14,35,37,40,52].…”
Section: Discussionsupporting
confidence: 57%
“…already at 15 minutes. This is at least two hours before changes in physiological responses that are typically associated with TSPO function [40]. Secondly, we found that within 15 minutes the classical TSPO ligand PK 11195 induces considerable changes in gene expression associated with the canonical pathway for modulation of gene expression in general.…”
Section: Discussionmentioning
confidence: 61%
“…Although a role for TSPO was not discussed in the new model, it remains to be explained how TSPO-binding chemicals could modulate cell death processes. The pharmacological evidence supporting a TSPO link to the MPTP appears well documented [22][23][24][25]. Developments in the field of the MPT were extensively described in a recent review on this topic [26].…”
mentioning
confidence: 99%
“…To address these concerns, Chelli et al [36] showed that impairments in GM cell line viability and mitochondrial membrane potential induced by PK 11195 were prevented when TSPO was silenced with siRNA. Costa et al [52] also showed GM cell line viability impairment induced by a high-affinity TSPO ligand was decreased by knocking down TSPO levels. The authors showed this compound did not affect ATP synthase activity in GM cells.…”
Section: Challenges and Future Workmentioning
confidence: 95%
“…These studies suggest, at least in vitro, the discrepancy between affinity and potency of anti-GM effects may be attributable to a mechanism other than nonspecificity. Recently, insight into what this mechanism may be was provided by Costa et al [52], who identified potency could be increased by increasing ligand residence time. A reversibly binding TSPO ligand that showed micromolar potency for impairing GM cell line viability could be transformed into a ligand that produced effects at low nanomolar doses by engineering it to covalently bind to TSPO.…”
Section: Challenges and Future Workmentioning
confidence: 99%